polymorphisms are associated with central precocious puberty and early puberty in girls - Sung Won Park; Seung-Tae Lee; Young Bae Sohn; Sung Yoon Cho; Se-Hwa Kim; Su Jin Kim; Chi Hwa Kim; Ah-Ra Ko; Kyung-Hoon Paik; Jong-Won Kim; Dong-Kyu Jin (Korean Pediatric Society, 2012)
PurposeSingle-nucleotide polymorphism (SNP) markers within LIN28B have been reported to be related to the timing of pubertal growth. However, no study has investigated the frequency of genetic markers in girls with precocious puberty (PP) or early puberty (EP). This study aimed to determine the frequency of putative genetic markers in girls with PP or EP.MethodsGenomic DNAs were obtained from 77 and 109 girls that fulfilled the criteria for PP and EP, respectively. The controls in this study were 144 healthy volunteers between 20 and 30 years of age. The haplotypes were reconstructed using 11 SNPs of LIN28B, and haplotype association analysis was performed. The haplotype frequencies were compared. Differences in the clinical and laboratory parameters were analyzed according to the haplotype dosage.ResultsEleven SNPs in LIN28B were all located in a block that was in linkage disequilibrium. The haplotype could be reconstructed using 2 representative SNPs, rs4946651 and rs369065. The AC haplotype was less frequently observed in the PP group than in the controls (0.069 vs. 0.144, P=0.010). The trend that girls with non-AC haplotypes tended to have earlier puberty onset (P=0.037) was illustrated even in the EP+PP patient group by Kaplan-Meier analysis.ConclusionThe results of the present study showed that non-AC haplotypes of LIN28B had a significant association with PP in girls.